2020
DOI: 10.3390/ijerph17041402
|View full text |Cite
|
Sign up to set email alerts
|

Passive Smoking Exposure in Living Environments Reduces Cognitive Function: A Prospective Cohort Study in Older Adults

Abstract: There is currently no consensus regarding the effects of passive smoking exposure on cognitive function in older adults. We evaluated 7000 permanent residents from six regions within Zhejiang Province, China, aged ≥60 years, without cognitive impairment at baseline and during follow-up examinations for two years. The Chinese version of the Mini-Mental State Examination was used to assess the participants’ cognitive function. Multivariate regression analyses were carried out to calculate the adjusted relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…PSE prevalence in our study was analogous to findings from similar studies in other settings [ 19 , 25 , 32 , 43 , 52 – 56 ]. For example, the prevalence of PSE was 36.1% in 2011 [ 19 ] and 31,1% in 2019 [ 53 ] in South Korea, 38.8% in Nigeria [ 52 ] and approximately 16–39% in India [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PSE prevalence in our study was analogous to findings from similar studies in other settings [ 19 , 25 , 32 , 43 , 52 – 56 ]. For example, the prevalence of PSE was 36.1% in 2011 [ 19 ] and 31,1% in 2019 [ 53 ] in South Korea, 38.8% in Nigeria [ 52 ] and approximately 16–39% in India [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, PSE accounts for approximately 3million deaths and dis-ability life adjusted years among about 11million people worldwide [ 29 ]. Further to this, PSE has been suggested to be associated with increased risk of some cancers [ 29 , 31 ], cognitive impairment [ 32 ], chronic kidney disease [ 33 ] and reduced coronary flow velocity reserve (CVFR) [ 34 ]. The pathophysiology of PSE and hypertension risk is multifaceted and yet to be clearly understood, but can be explained in several ways,…”
Section: Discussionmentioning
confidence: 99%
“…Brain studies reveal a thinner anterior cingulum and prefrontal lobe, and many other structural abnormalities in smokers [37]. Passive smoking increases the risk of cognitive impairment in older adults by 24% and this seems to be especially prominent with non-smokers [38]. Cigarette smoking at an earlier age appears to predict the onset of cognitive impairment at an older age [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in China indicated that SHS exposure increased the risk of cognitive impairment in older adults. 16 17 Nevertheless, both these studies only used two-wave longitudinal data and did not control for baseline cognition. 16 17 Therefore, the primary aim of this study was to investigate the relationship between SHS and cognitive function among older non-smoking Chinese women, using three-wave longitudinal national representative data.…”
Section: Introductionmentioning
confidence: 99%
“… 16 17 Nevertheless, both these studies only used two-wave longitudinal data and did not control for baseline cognition. 16 17 Therefore, the primary aim of this study was to investigate the relationship between SHS and cognitive function among older non-smoking Chinese women, using three-wave longitudinal national representative data. Through the classification of respondents by different years of SHS exposure in a 4-year panel, we identified whether certain high SHS exposure groups were at higher risk of cognitive decline than others after controlling for confounders.…”
Section: Introductionmentioning
confidence: 99%